'Italswebquest': a wiki as a platform of collaborative blended language learning and a course management system. (26th January 2010) - Perifanou, Maria A.; Mikros, George K.
The advent of Web 2.0 has caused a significant change in the way the technology is used in all the fields of education as it is characterised by social learning, active participation and easy to use tools. Web 2.0 could offer a turning point in language teaching methodology. Wiki is a major component of Web 2.0 and can particularly involve language learners in their construction of knowledge. This paper presents a case study in which a wiki was used both as a platform of collaborative blended language learning and as a course management system in an Italian course of future Italian language teachers. Results have confirmed most of the research questions of this study and one of the major findings was the increase of students' interest, motivation and participation during the whole project.